AN ANALYSIS OF COMPENSATION TECHNIQUES REGARDING TRANSLATION LOSS AND CAPTIONING GUIDELINES IN THE SUBTITLE OF MERANTAU - Stiasih, Yanriski (2013)
The study entitled An Analysis of Compensation Techniques Regarding Translation Loss and Captioning Guidelines in the Subtitle of "Merantau" focuses on the translation and captioning techniques which are applied in English Subtitle of "Merantau" film. Qualitative descriptive method is used in this study to uncover the findings using Hervey and Higgins' (1992) concept of compensation techniques and Karamitroglou's (1998) captioning guidelines. The findings show that the translator uses mostly compensation in kind. It may show that the translator might find the equal expression in target language that is more acceptable. In addition, the translated script has fulfilled the standards of captioning.